Manajemen Strategis Pengembangan Sekolah Menengah Kejuruan di Lembaga Pesantren (Studi Kasus di SMK Islam Nurul Qolbi YPP Nurul Qolbi Setanggor) - Muhamad haidir (Universitas Islam Negeri (UIN) Mataram, 2022)
This study aimed to discover environmental analysis, and formulation of vocational high school development strategies in Islamic educational institutions. Thus, this qualitative research with a multi-case study approach gathered data through observation, interviews, and documentation. Data were then analyzed with collections, condensation, presentation, and data verification. Moreover, each case was discussed to figure out patterns and meaning related to the research and systematically reported a single case. Finally, the data obtained are checked with credibility transferability, comparability, and dependability standards. Environmental analysis by identifying the external environment shows that there has been a social change in the community, the extent of the work of the adolescent moral degradation due to the existence of Zainuddin Abdul Majid International Airport (BIZAM) and the Mandalika, the competition to get jobs, other vocational competitors. Furthermore, they mapped the internal power of the historical, capital, and geographical graduates of S-1 as teaching staff. (2) strategy formulation by way of; a) Strategy to answer opportunities and challenges; b) The vision and mission illustrate the hope of making SMKs (Vocational High School) print religious, competent, and independent generation; c) SMKs can be enjoyed by all society levels; d) Strengthening branding; f) The existence of student embryos.